Pengenalan E-Modul dalam Penggunaan Aplikasi Canva untuk Membuat Bahan Ajar pada Program Kreativitas Mahasiswa (PKM) - Theresia Evy Yulianty Nadeak; Dewi Mustari; Retna Ningsih (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The use of technology in education is essential, particularly in creating digital teaching materials. This Community Service (PKM) activity aimed to introduce teachers and educators to the process of creating e-modules using Canva, a user-friendly tool with templates, graphics, and features for designing interactive and visually engaging teaching materials. The training provided hands-on experience, enabling participants to create curriculum-aligned e-modules, enhancing both their teaching materials and student engagement. The goal was to equip educators with the skills to develop innovative, digital-friendly materials that cater to various learning styles. During the training, participants integrated multimedia elements like images, videos, and text to make the learning experience more interactive. Emphasis was placed on incorporating technology in both physical classrooms and online learning environments, improving the overall dynamic of lessons. The training also helped educators gain a deeper understanding of Canva as a versatile tool for educational purposes. Results showed significant improvement in participants' confidence and ability to use Canva effectively to create engaging and pedagogically sound materials. Many expressed that the skills gained would help them incorporate creative and interactive elements into their lessons, fostering a more dynamic learning environment. This PKM activity successfully empowered participants to enhance their digital competencies and adapt to the evolving educational landscape. It contributed to improving the quality of education, ensuring educators are better prepared to navigate the digital age and meet the needs of modern learners. Furthermore, the training emphasized continuous learning and adapting to new technological tools to improve teaching strategies and learning outcomes